Hubungan sikap dan posisi kerja dengan low back pain pada perawat RSUD Purbalingga - Fatoni, Himawan; Handoyo; Swasti, Keksi Girindra (Jurnal Keperawatan Soedirman, 2012)
Low back pain is the pain suffered in under side of waist and able to spread into the leg, specifically in its backsides and outer parts. One of its causes is musculoskeletal problems caused by not well body activities done. The purpose of this research is for seeing whether the correlation of job posture and position with low back pain suffered by the nurses in Purbalingga Hospital. 32 respondents fulfilling inclusion criteria who are chosen through purposive sampling. The research instrument implements the use of Ovako Working Posture Analysis System (OWAS) for testing job posture and position and laseque test for testing low back pain. Its data processing implements the use of frequency distribution through Chi Square statistic test. From 32 respondents researched, 10 respondents have job posture and position that is possible for causing musculoskeletal injuries and 6 respondents suffering low back pain. That isn’t correlation between job attitude and position with low back pain